Characterisation of L-malic acid metabolism in strains of Saccharomyces and the development of a commercial wine yeast strain with an efficient malo-ethanolic pathway - Volschenk, Heinrich (Stellenbosch : Stellenbosch University, 2012)
Dissertation (PhD)--University of Stellenbosch, 2002.